Looking for answers? Westonci.ca is your go-to Q&A platform, offering quick, trustworthy responses from a community of experts. Experience the ease of finding quick and accurate answers to your questions from professionals on our platform. Get quick and reliable solutions to your questions from a community of experienced experts on our platform.
Sagot :
To divide the polynomial [tex]\( P(x) = 8x^2 - 3x - 17 \)[/tex] by [tex]\( D(x) = 4x - 1 \)[/tex], we can use polynomial long division. Our goal is to express the quotient in the form:
[tex]\[ \frac{P(x)}{D(x)} = Q(x) + \frac{R(x)}{D(x)} \][/tex]
where [tex]\( Q(x) \)[/tex] is the quotient and [tex]\( R(x) \)[/tex] is the remainder.
Let's go through the steps in polynomial long division:
1. Setup: Write the division as:
[tex]\[ \frac{8x^2 - 3x - 17}{4x - 1} \][/tex]
2. First Division:
- Divide the leading term of the numerator [tex]\( 8x^2 \)[/tex] by the leading term of the denominator [tex]\( 4x \)[/tex]. This gives:
[tex]\[ \frac{8x^2}{4x} = 2x \][/tex]
- Multiply the entire divisor by [tex]\( 2x \)[/tex]:
[tex]\[ (4x - 1) \cdot 2x = 8x^2 - 2x \][/tex]
- Subtract this result from the original polynomial:
[tex]\[ (8x^2 - 3x - 17) - (8x^2 - 2x) = -x - 17 \][/tex]
3. Second Division:
- Divide the new leading term [tex]\( -x \)[/tex] by the leading term of the divisor [tex]\( 4x \)[/tex]:
[tex]\[ \frac{-x}{4x} = -\frac{1}{4} \][/tex]
- Multiply the divisor by [tex]\(-\frac{1}{4}\)[/tex]:
[tex]\[ (4x - 1) \cdot -\frac{1}{4} = -x + \frac{1}{4} \][/tex]
- Subtract this result from the polynomial:
[tex]\[ (-x - 17) - (-x + \frac{1}{4}) = -17 - \frac{1}{4} = -\frac{68}{4} - \frac{1}{4} = -\frac{69}{4} \][/tex]
So, our quotient ([tex]\( Q(x) \)[/tex]) and remainder ([tex]\( R(x) \)[/tex]) are:
[tex]\[ Q(x) = 2x - \frac{1}{4}, \quad R(x) = -\frac{69}{4} \][/tex]
Therefore, we can write the division as:
[tex]\[ \frac{P(x)}{D(x)} = 2x - \frac{1}{4} + \frac{-\frac{69}{4}}{4x - 1} \][/tex]
In a more simplified form, it will be:
[tex]\[ \frac{P(x)}{D(x)} = 2x - \frac{1}{4} + \frac{-69}{4(4x - 1)} \][/tex]
[tex]\[ \frac{P(x)}{D(x)} = Q(x) + \frac{R(x)}{D(x)} \][/tex]
where [tex]\( Q(x) \)[/tex] is the quotient and [tex]\( R(x) \)[/tex] is the remainder.
Let's go through the steps in polynomial long division:
1. Setup: Write the division as:
[tex]\[ \frac{8x^2 - 3x - 17}{4x - 1} \][/tex]
2. First Division:
- Divide the leading term of the numerator [tex]\( 8x^2 \)[/tex] by the leading term of the denominator [tex]\( 4x \)[/tex]. This gives:
[tex]\[ \frac{8x^2}{4x} = 2x \][/tex]
- Multiply the entire divisor by [tex]\( 2x \)[/tex]:
[tex]\[ (4x - 1) \cdot 2x = 8x^2 - 2x \][/tex]
- Subtract this result from the original polynomial:
[tex]\[ (8x^2 - 3x - 17) - (8x^2 - 2x) = -x - 17 \][/tex]
3. Second Division:
- Divide the new leading term [tex]\( -x \)[/tex] by the leading term of the divisor [tex]\( 4x \)[/tex]:
[tex]\[ \frac{-x}{4x} = -\frac{1}{4} \][/tex]
- Multiply the divisor by [tex]\(-\frac{1}{4}\)[/tex]:
[tex]\[ (4x - 1) \cdot -\frac{1}{4} = -x + \frac{1}{4} \][/tex]
- Subtract this result from the polynomial:
[tex]\[ (-x - 17) - (-x + \frac{1}{4}) = -17 - \frac{1}{4} = -\frac{68}{4} - \frac{1}{4} = -\frac{69}{4} \][/tex]
So, our quotient ([tex]\( Q(x) \)[/tex]) and remainder ([tex]\( R(x) \)[/tex]) are:
[tex]\[ Q(x) = 2x - \frac{1}{4}, \quad R(x) = -\frac{69}{4} \][/tex]
Therefore, we can write the division as:
[tex]\[ \frac{P(x)}{D(x)} = 2x - \frac{1}{4} + \frac{-\frac{69}{4}}{4x - 1} \][/tex]
In a more simplified form, it will be:
[tex]\[ \frac{P(x)}{D(x)} = 2x - \frac{1}{4} + \frac{-69}{4(4x - 1)} \][/tex]
Thanks for stopping by. We are committed to providing the best answers for all your questions. See you again soon. Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. Stay curious and keep coming back to Westonci.ca for answers to all your burning questions.